The prevalence and predictors of HIV-hypertension comorbidity among youth living with HIV in South Africa, 2010-2016 - Makuapane, Lerato Patricia (My University, 2018)
Over the last two decades, AIDS mortality rates has decreased substantially due to extensive HIV treatment in South Africa, which left HIV as a chronic illness. Therefore, since the disease nature of HIV predisposes patients to other clinical conditions; many HIV patients also suffers from other AIDS-related and non-AIDS diseases resulting in comorbidities. It is most prevalent among population aged 14-35 years. At the same time, NCDs are rapidly increasing among youth with hypertension being amongst the leading cause of HIV comorbidities. High prevalence of both HIV/ AIDS and hypertension in this cohort rise a concern of their simultaneous occurrence to develop HIV-hypertension comorbidity. Abbreviation abstract)
THIS RESEARCH IS SUBMITTED IN PARTIAL FULFILMENT OF MASTERS OF ARTS IN HEALTH DEMOGRAPHY AT UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG.
Keywords: HIV; Hypertension; Comorbidity